Nivel de conocimientos y prácticas de medidas de bioseguridad en internos de enfermería del hospital Minsa II-2 Tarapoto Junio - Agosto 2012 - López Alarcón, Renzo Daniel (2012)
The present research on "knowledge level and biosecurity practices in the internal MOH Hospital Nursing II-2 Tarapoto. June to August 2012, was raised as simple descriptive research cross section with a quantitative approach, it aimed to determine the level of knowledge and practice biosecurity measures internal MOH Hospital nursing Tarapoto II-2 June - August 2012. The sample was represented by 21intemal MOH Hospital nursing Tarapoto II-2, who met the inclusion criteria. To collect the information was used as the survey method and two instruments: the questionnaire was structured to determine the level of knowledge about biosecurity measures in nursing internal MOH Hospital II-2 Tarapoto and checklist determine the level of biosecurity practices in them. The data were systematized using the Microsoft Excel statistical package SPSS version 17.0 2007. and findings included: 48% of nursing interns were between 23 to 24 years, 86% had normal general knowledge level biosecurity measures, 10% good and 5% level of knowledge bad. Regarding the level of general practice biosecurity measures internal nursing 57% performed regular practice, the 38% general good practices and bad practices in 5% biosecurity measures on that basis we believe it is necessary to use Post-exposure Prophylaxis in nursing internal view, the situation Is dramatically presented by students regarding protection against biological hazards, as there is no social security coverage for the same, and rampant ignorance and lack of interest , this event deserves awareness and promoting a culture of self-care